An Experimental Investigation on Reverse Direction Micellar Electrokinetic Capillary Chromatography, Hydrostatic Flow Injection and Diffusional Injection - Ghowsi, Kiumars; Ghowsi, Hosein (Challenges and Advances in Chemical Science Vol. 3, 2021)
Dunn, Hankins, and Ghowsi observed separation in the case where ions incapillary electrophoresis migrate in the opposite direction of electroosmosis and ions travel faster than flow, eventually separating them and reaching the detector.For the separation of p-xylene and toluene, a similar form of electrokinetic chromatography called reverse direction MECC has been developed (micellar electrokinetic capillary chromatography).In reverse direction micellar electrokinetic capillary chromatography, the influence of injection time on separation is explored. Hydrostatic and diffusion injection were investigated in this study.